Prevalence of oncogenic human papillomavirus (HPV 16/18) infection, cervical lesions and its associated factors among women aged 21-49 years in Amhara region, Northern Ethiopia. - Minwuyelet Maru Temesgen; Tefera Alemu; Birtukan Shiferaw; Seid Legesse; Taye Zeru; Mahteme Haile; Tesfaye Gelanew (PLoS ONE)
Background Human papillomavirus (HPV) infection is considered as the major risk factor for the development of cervical cancer, second most frequent cancer in Ethiopia. However, the magnitude of the problem and the associated factors remain unrevealed in the Amhara region. This study aimed to determine the prevalence of HPV infection and factors contributing to the progression of HPV infection to cervical cancer. Methods Facility-based cross-sectional study design was employed among women aged 21 to 49 years of age who came for routine cervical cancer screening to 4 randomly selected hospitals (2 general and 2 referral) of Amhara region from May to October, 2019. The sample size was calculated by using the single population proportion formula, proportionated to hospitals, and women were recruited consecutively. Socio demographic and clinical data were collected using a pretested questionnaire and detection of HPV infection was done using HPV test (OncoE6TM Cervical Test) specific to HPV16/18 in cervical swabs. Visual inspection with acetic acid (VIA) was used to determine cervical lesions (precancerous and cancerous). Descriptive statistics and bivariate and multivariate logistic regression were used to describe HR-HPV and cervical lesions burden and association between HR-HPV, and cervical lesions and potential risk factors. Results Among 337 women 21 to 49 years (median age of 35 years ±SD = 7.1 years) of age enrolled in the study, The overall prevalence of oncogenic HPVs (HPV16/18) and the VIA-positivity rate, possible an indicative of cervical lesions, were 7.1% and 13.1%, respectively. Logistic regression analysis showed a significant association between early age of first sexual intercourse (COR = 2.26; 95% CI: 1.0-5.05) and level of education (COR = 0.31; 95% CI: 0.12-0.78) with cervical lesions. Higher odds of HPV positivity (COR = 1.56; 95% CI: 0.59-4.11, p = 0.36) and VIA positivity (COR = 1.39; 95% CI: 0.64-3.00, p = 0.39) were observed among participants who had a history of sexually transmitted illnesses (STIs). Conclusions There was a relatively low prevalence of oncogenic HPV 16/18 and VIA-positivity in women attending four hospitals in the Amhara Region. Early age sexual contact, high parity, and being uneducated/low level of education were independently associated factors with HR-HPV infection and development of cervical lesions, highlighting the importance of prioritizing the limited HPV testing to those risk groups.